In vitro antimicrobial activity of root canal sealers and calcium hydroxide paste - Alessandro L Cavalcanti; Francisco I.R. Limeira; Eveline A.L.S. Sales; Ana A.G. Oliveira; Dened M.B. Lima; Ricardo D Castro (Wolters Kluwer Medknow Publications, 2010)
Aim: To evaluate the in vitro antimicrobial activity of different root canal sealers and calcium hydroxide (CH) paste. Materials and Methods: The sample was composed of two sealers (Fill Canal® and Sealer 26® ), one CH cement (Hydro C® ), and a CH paste. The agar diffusion test was performed in Petri dishes inoculated with the following microorganisms: Streptococcus salivarius, Streptococcus oralis, Streptococcus mitis, Lactobacillus casei, Streptococcus mutans, Candida albicans, Candida krusei, and Candida tropicalis. The diameters of the zones of microbial growth inhibition were measured after 24 h. The tests were performed in triplicate. Data were analyzed statistically by ANOVA and Tukey's test at 5% significance level. Results: Fill Canal® exhibited the largest mean zone of microbial growth inhibition against the Candida species and differed significantly from the other groups (P < 0.001). When inhibition was observed against S. mitis and S. oralis, the CH paste presented a larger mean zone of microbial growth inhibition than those of the other materials (P < 0.05). Regarding the inhibition of S. mutans, a statistically significant difference was observed only between the CH paste and Hydro C® (P < 0.05); the paste produced the largest mean zone of microbial growth inhibition against this microorganism. Regarding the inhibition of S. salivarius, Fill Canal® presented smaller mean zone of microbial growth inhibition than Sealer 26® and CH paste (P < 0.05). Conclusion: All the materials presented zones of microbial growth inhibition against all the test bacteria. Fill Canal® presented the largest mean zone of inhibition against the Candida species. For the Streptococcus cultures, none of the sealers presented inhibition superior to that of the CH paste.